Analysis of proton irradiated n- and p-type strained FinFETs at low temperatures down to 100 K. (25th April 2018) - Caparroz, Luis Felipe Vicentis; Bordallo, Caio Cesar Mendes; Martino, Joao Antonio; Simoen, Eddy; Claeys, Cor; Der Agopian, Paula Ghedini
Abstract: This paper studies the main low temperature electrical parameters of SOI n- and p-type FinFETs, standard and strained devices, submitted to proton irradiation. The study covers the range from room temperature down to 100 K, focusing on the threshold voltage (VTH ), subthreshold swing (SS), the Early voltage VEA, transistor efficiency and the intrinsic gain voltage (AV ) for 3 different channel widths. The p-channel devices showed a greater immunity to radiation than the n-channel ones, when considering the basic parameters thanks to the back conduction turn-off tendency, while from the analog parameters point of view, both transistor types presented a similar response to proton radiation at strong inversion.